2022
DOI: 10.3390/d14070546
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Differentiation and Structure of Maruca vitrata (Lepidoptera: Crambidae) in India

Abstract: Maruca vitrata is one of the primary biotic constraints for pigeon pea production in India. The present study assessed the genetic variation and population structure of M. vitrata from diverse agro-ecologies in India using the mitochondrial cytochrome c oxidase I gene. A low number of segregating sites (10), haplotypes (13), nucleotide diversity (0.00136), and overall mean genetic distance (0.0013) were observed among the populations. The negative values of the neutrality tests and unimodal mismatch distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Based on the molecular characterization with RAPD markers (Deepa and Srivastava, 2011) and COI gene (Chakravarty et al, 2021), phenotyping of immature and adult stages Chakravarty et al, 2023b), and other biological traits (Chakravarty et al, 2019 and2023a), existence of sub-specific level variations among Helicoverpa armigera populations from diverse agro-ecologies of India has been deciphered. Similar studies for Leucinodes orbonalis (Padwal et al, 2022), Spodoptera litura (Ganguly et al, 2023) and Maruca vitrata (Mahalle et al, 2022) revealed genetic homogeneity for these pest species in the country. Further, Mahalle et al (2023) have also screened publically accessible expressed sequence tag resources to identify microsatellites and evaluate their suitability as DNA markers for investigating gene flow patterns among populations of M. vitrata from pigeonpea fields throughout India.…”
Section: O N L I N E C O P Ysupporting
confidence: 61%
“…Based on the molecular characterization with RAPD markers (Deepa and Srivastava, 2011) and COI gene (Chakravarty et al, 2021), phenotyping of immature and adult stages Chakravarty et al, 2023b), and other biological traits (Chakravarty et al, 2019 and2023a), existence of sub-specific level variations among Helicoverpa armigera populations from diverse agro-ecologies of India has been deciphered. Similar studies for Leucinodes orbonalis (Padwal et al, 2022), Spodoptera litura (Ganguly et al, 2023) and Maruca vitrata (Mahalle et al, 2022) revealed genetic homogeneity for these pest species in the country. Further, Mahalle et al (2023) have also screened publically accessible expressed sequence tag resources to identify microsatellites and evaluate their suitability as DNA markers for investigating gene flow patterns among populations of M. vitrata from pigeonpea fields throughout India.…”
Section: O N L I N E C O P Ysupporting
confidence: 61%
“…Such levels of low genetic diversity have also been documented for other lepidopteran insects like Diatraea saccharalis, which was found to have Ho ranging from 0.08 to 0.88 with a mean of 0.42, and He ranged from 0.12 to 0.63 with a mean of 0.49 [61], whereas, for Carposina sasakii, Ho and He ranged from 0.00 to 0.68 and 0.06 to 0.77, respectively [47]. Population genetic structure analysis revealed low genetic differentiation (average F ST = 0.046, p < 0.005) and lack of genetic structure in Indian M. vitrata, probably due to the occurrence of high gene flow between the different sampled regions [5]. The results demonstrated that gene flow between M. vitrata populations in India is not confined because the genetic divergences were mainly found between the individuals.…”
Section: Discussionmentioning
confidence: 90%
“…It is also reported to cause yield losses of 20 to 80% in infested pigeonpea fields and may lead to total crop failure without proper insect population management [3]. Legume farmers rely primarily on chemical insecticides as the primary control method to tackle M. vitrata damage [5]. However, the extensive utilization of insecticides has increased resistance in this pest species against them, thereby leading to population outbreaks and rendering its management more difficult [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intraspecific diversity of the crambid moth Maruca vitrata in India was the focus of another study [27]. This species is of the one of the most destructive pests of grain legumes across the subtropical and tropical regions of the world, and hence knowledge on intraspecific diversity is important for its management.…”
mentioning
confidence: 99%